COMPLETE SYSTEM OF EQUALIZATIONS OF CONDITIONAL EQUILIBRIUM OF AREAS OF BORING COLUMN IN MINING HOLE ORIENTED ARBITRARILY IN SPACE - Мойсишин, Василь Михайлович; Векерик, Василь Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
At this work common equalizations of equilibrium of area of boring column of oriented are shown out in space arbitrarily; the distributed are taken into account on length of force of weight, friction of pipes o walls of mining hole, motion of washing liquid, rotator and forward motions of column. The features of formation of flat and spatial forms of equilibrium of resilient line of boring column are trained, dependences are got for finding of its crooked and twisting, the kinematics of rotation of areas of columns and motion of washing liquid in pipes and out of pipes is trained space.